Bahasa Positivistime Logis dan Maknanya Bagi Agama : Kajian Pemikiran Rudolf Carnap - Samsuri - (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2003)
This paper explores Rudolf Carnap's thought, an exponentand member of the Vienna Circle, on the logical positivisme philosophy. As most known, the logical positivism has influenced the natural science acceleration. Social and humanity sciences, including religion studies, have been dominated by physicalism of natural science methods which was developed on logical positivism ideas. Carnap's main works concerned on language and logics, semantics, and syntax. On logical positivism, Carnap's thought could be looked at in three sections: verification and confirmation, elimination of metaphysics, and imified of science (scientism). Its implication for religious living is the problem of meaning the religion texts according to logical positivism propositions, which be concluded that the propositions/texts of religion teaching have not meaning if they could be not verified or obeserved.